Mengembangkan konsep manajemen risiko yang efektif di bank syariah - Kamalia, Isna (Maliki Interdisciplinary Journal, 2024)
The risks faced by sharia banks are not the only traditional risks such as market risk, credit risk, operational risk and liquidity risk, but sharia banks face other risks such as sharia compliance risk, financing risk, yield risk, investment risk, and so on. In achieving the goals and objectives that have been set in facing global competition, sharia banking is required to continue to use the identity of a sharia financial company in accordance with sharia principles and compliance.